Ectopic premolar tooth in the maxillary sinus: A case report and review of literature - K S Gangadhara Somayaji; Aroor Rajeshwary; Mohammad Nalapad Abdulla; Sherwak Ramlan (Archives of Medicine and Health Sciences, 2013)
Ectopic eruption of teeth in non-dental sites is a rare phenomenon and such cases have been reported to occur in the nasal cavity, chin, maxillary sinus, mandible, palate, and orbital cavity. Ectopic tooth eruptions in maxillary sinus are usually asymptomatic or may present with recurrent sinusitis. Majority are found incidentally during routine clinical or radiological investigation. We present a case of an ectopic upper second premolar tooth that caused chronic purulent sinusitis in relation to the right maxillary sinus. The tooth was attached to the posterior wall of the sinus without an associated dentigerous cyst. The case was innovatively managed by endoscopic approach through sublabial route.